2022
DOI: 10.1186/s12864-022-09071-w
|View full text |Cite
|
Sign up to set email alerts
|

NSD1 gene evolves under episodic selection within primates and mutations of specific exons in humans cause Sotos syndrome

Abstract: Background Modern human brains and skull shapes differ from other hominids. Brain growth disorders as micro- (ASPM, MCPH1) and macrocephaly (NFIX, GLI3) have been highlighted as relevant for the evolution in humans due to the impact in early brain development. Genes associated with macrocephaly have been reported to cause this change, for example NSD1 which causes Sotos syndrome. Results In this study we performed a systematic literature review, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The missense variant, NSD1 (NM_022455): c.6397T > G(p.C2133G), in Case 4 resides in the plant homeodomain (PHD) 5 domain of the NSD1 protein, exhibiting considerable conservation across species. PHD acts as a C4HC3 zinc finger-like motif within nuclear proteins that are involved in chromatin modulation and epigenetics [ 29 ]. This variant significantly influenced local hydrogen bond formation, potentially compromising the stability of the protein’s three-dimensional structure.…”
Section: Discussionmentioning
confidence: 99%
“…The missense variant, NSD1 (NM_022455): c.6397T > G(p.C2133G), in Case 4 resides in the plant homeodomain (PHD) 5 domain of the NSD1 protein, exhibiting considerable conservation across species. PHD acts as a C4HC3 zinc finger-like motif within nuclear proteins that are involved in chromatin modulation and epigenetics [ 29 ]. This variant significantly influenced local hydrogen bond formation, potentially compromising the stability of the protein’s three-dimensional structure.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published studies have confirmed that patients with HMT SETD2 mutations present with intellectual disability, developmental delay, and skeletal system abnormalities as the main clinical manifestations [ 101 ]. However, mutations in the domain between HMT NSD1 exon 10 and 22 are associated with microcephaly [ 102 ]. The above evidence suggests that histone methyltransferases are closely associated with neurodevelopmental disorders.…”
Section: Role Of Chromatin Modifiers In Human Diseasesmentioning
confidence: 99%